Commitment, employee engagement and readiness to change among oil palm plantation officers - Zulkarnain Zulkarnain; Sherry Hadiyani; Eka D.J. Ginting; Fahmi Fahmi (SA Journal of Human Resource Management, 2024)
Orientation: Organisations must continually adapt to the external environment to remain competitive. However, employees often resist change because of fear and uncertainty.